An Analysis of Using Numbered Head Together Learning Model in Geography Subject at Class X IPS 5 Class in SMA 1 Luhak Nan Duo - Muhammad Hakim; Lusi Hervina; Khairani Khairani (Postgraduate School, Universitas Negeri Padang, 2020)
The aims of this research were to reveal the data, information and discuss the using of Numbered Head Together Learning Model of Geography at X IPS 5 Class in SMAN 1 Luhak Nan Duo. The type of the research was a descriptive research with a quantitative approach. This research was conducted at SMAN 1 Luhak Nan Duo through the subject of this research being students at Class X IPS 5, amounting to 33 students. Data collection was done through observation sheets, questionnaires, and documentation. The data technique analysis was the quantitative descriptive by the calculation of the percentage and total respondents' achievements. The conclusion of this research was the students' response to the application of the learning model of the Numbered Head Together at X IPS 5 Class of SMAN 1 Luhak Nan Duo was in the much-needed category and was in the very good category.